Resposta :
Resposta:
A) S = -5/3 P = 2/3
B) S = 6/9 P = 1/9
C) S = -11/2 P = -1/2
D) S = 5/7 P = -3/7
Explicação passo-a-passo:
A fórmula da soma é " S = -b/a ", e do produto é: " P = c/a ". Assim sendo, é só substituir e ser feliz :)
a)
[tex]P = \frac{c}{a} = \frac{2}{3} \\S = -\frac{b}{a} = -\frac{5}{3}[/tex]
b)
[tex]P = \frac{c}{a} = \frac{1}{9} \\S = -\frac{b}{a} = -\frac{-6}{9} = \frac{2}{3}[/tex]
c)
[tex]P = \frac{c}{a} = \frac{-1}{2} = -\frac{1}{2}\\S = -\frac{b}{a} = -\frac{11}{2}[/tex]
d)
[tex]P = \frac{c}{a} = \frac{-3}{7} = -\frac{3}{7}\\S = -\frac{b}{a} = -\frac{-5}{7} = \frac{5}{7}[/tex]